Adsorpsi Gas CO Pada Gas Buang Sepeda Motor Menggunakan Biochar dari Cangkang Buah Karet: indonesia - -, nur faizah; -, Aryo Sasmita; Elvie Yenie (Jurnal Sains dan Teknologi Lingkungan, 2025)
Biochar is often used as a material to make adsorbents. The largest contributor to air pollution is transportation emissions which have a negative impact on the environment and human health.  Efforts to reduce emissions from transportation, especially motorized vehicles, are using biochar. Biochar is in the form of a solid precipitate which has a large surface area and is obtained from thermal decomposition of biomass without using oxygen or in limited oxygen conditions which contains carbon so it has a high absorption capacity which can be used as an adsorbent. This research aims to analyze the effect of variations in the shape of the adsorbent on the adsorption of CO gas in motorbike exhaust gas using biochar from rubber fruit shells. Biochar was prepared by carbonization process at 5000C for 1 hour using 10% H3PO4 activator and sieving with 100 mesh sieve. The biochar product was then tested using proximate analysis. Proximate analysis results show biochar complies with SNI 06-3730-1995 with a water content value of 5%; ash content 4.2%; volatile matter 4.5%; and fixed carbon 86.3%. The results showed that the highest allowance for CO gas emissions on motorbikes occurred in the first test of 73.768% with a tube shape and a media length of 3 cm. The best adsorption capacity value occurred in the first test with a length of 3 cm biochar media, namely 138.738 mg/g. The results of this study concluded that biochar from rubber fruit shells met quality standards and could be used as an alternative absorbent for gas emissions from motorcycles.